2022
DOI: 10.1590/1980-5373-mr-2021-0390
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Strenx 900 Steel Using Electrical Discharge Alloying Process with Cu-10Ni- CrxPowder Metallurgy Sintered Electrode

Abstract: The present investigation aims to coat the layer with Nickel (Ni) and Copper (Cu)over the surface of strenx 900 steel using semi sintered Cu-10Ni-Cr x electrodes(x = 2, 4 & 6 wt. %). Three different proportions of semi sintered electrodes such as, Cu-10Ni-2 weight percentage of Chromium (Cr), Cu-10Ni-4 wt. % Cr,and Cu-10Ni-6 wt. % Cr were prepared by powder metallurgy route. Electric discharge alloying was completed based on L 9 orthogonal array and alloyed parameters were optimized using Taguchi method. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The study indicated the influence of the tool material on the workpiece, and it was observed that the surface finish was below the acceptable limit, with values exceeding 10 microns. Sridhar et al [154] attempted the electrical discharge modification process using a Cu-10Ni-Cr sintered P/M electrode for the surface modification of Strenx 900 steel. Their study suggested that chromium, copper and nickel were deposited on the workpiece.…”
Section: Powder Metallurgy Edm Electrodementioning
confidence: 99%
“…The study indicated the influence of the tool material on the workpiece, and it was observed that the surface finish was below the acceptable limit, with values exceeding 10 microns. Sridhar et al [154] attempted the electrical discharge modification process using a Cu-10Ni-Cr sintered P/M electrode for the surface modification of Strenx 900 steel. Their study suggested that chromium, copper and nickel were deposited on the workpiece.…”
Section: Powder Metallurgy Edm Electrodementioning
confidence: 99%